Assessment of urban heat Islands in small- and mid-sized cities in Brazil - Cardoso, Renata dos Santos [UNESP]; Dorigon, Larissa Piffer [UNESP]; Teixeira, Danielle Cardozo Frasca [UNESP]; Amorim, Margarete Cristiane de Costa Trindade [UNESP] (MDPI, 2017)
Urban heat islands (UHIs) in large cities and different climatic regions have been thoroughly studied; however, their effects are becoming a common concern in smaller cities as well. We assessed UHIs in three tropical cities, analyzing how synoptic conditions, urban morphology, and land cover affect the heat island magnitude. Data gathering involved mobile surveys across Paranavaí (Paraná), Rancharia (São Paulo), and Presidente Prudente (São Paulo), Brazil, during summer evenings (December 2013-January 2014). Temperature data collected over five days in each city point to heat islands with magnitudes up to 6 °C, under calm synoptic conditions, whereas summer average UHI magnitudes peak at 3.7 °C. In addition, UHI magnitudes were higher in areas with closely spaced buildings and few or no trees and building materials that are not appropriate for the region's climate and thermal comfort.
Keywords: Mobile traverses; Tropical cities; Urban climate; Urban heat island